Human umbilical cord mesenchymal stem cells contribute to the reconstruction of bladder function after acute spinal cord injury via p38 mitogen-activated protein kinase/nuclear factor-kappa B pathway. Issue 3 (1st March 2022) - Li, Jue; Huang, Jiliang; Chen, Ling; Ren, Wei; Cai, Wenzhi
ABSTRACT: The association between spinal cord injury (SCI) and bladder symptoms has been intensively described. Human umbilical cord mesenchymal stem cell (hUC-MSC) treatment is beneficial to the recovery of bladder function after SCI, but its mechanism is unclear. We established an SCI model, and prepared hUC-MSCs in advance, followed by verification using flow cytometry. The Basso, Beattie and Bresnahan (BBB) score and urodynamic index were employed to evaluate motor function and bladder functions, respectively. Hematoxylin–eosin staining, luxol fast blue staining, and Masson's trichrome staining were utilized to assess pathological changes. Real-time quantitative PCR and Western blot were used to determine the mRNA and protein expressions in bladder tissues. The immunophenotypes of the HUC-MSCs were CD90 + and CD105 +, but CD34 −, CD45 − and HLA-DR − . Rats appeared severe motor dysfunction after SCI, but the BBB score was increased in hUC-MSCs after the second week. Pathologically, the improvement of the lesion area on the dorsal spinal cord, augmented anterior gray horn neuron cells of the spinal cord and lessened bladder tissue remodeling (fibrosis, collagen deposition) as well as modulated inflammation could be observed. Besides, SCI increased bladder weight, bladder capacity, urine volume and residual urine volume, and decreased urination efficiency. HUC-MSCs ameliorated SCI-induced pathological changes and bladder functions, the expressions of Collagen I, Collagen III, fibroblast growth factor 2 (FGF2), phospho-p38, transient receptor potential vanilloid 1, Toll-like receptor 4 and phospho-nuclear factor-kappa B (p-NF-κB). To sum up, HUC-MSCs contribute to the reconstruction of bladder function after SCI by repressing p38 MAPK/NF-κB pathway. Graphical abstract: uf0001